Population dynamics of Malabar sole Cynoglossus macrostomus Norman along Calicut coast - Khan, M Feroze; Nandakumaran, K (Indian Journal of Fisheries, 2011)
The flatfishes constitute a major fishely along Calicut coast and enjoy considerable local importance next to oilsardine and mackerel. Norman (1927, 1928) described 91 species, of which only a few form fishery of local importance. The most important species in the commercial fishery is Cynoglossus macrostomus Norman, locally known as mantha